Effect of Auricularia auricula polysaccharide on characteristic structure, rheological properties, and tensile texture in whole wheat dough. Issue 11 (13th September 2022) - Du, Yifei; Li, Wen; Mariga, Alfred Mugambi; Fang, Yong; Sun, Xinyang; Hu, Qiuhui; Pei, Fei
Abstract: In this study, the effects of Auricularia auricula polysaccharide ( Aa p) on the quality of whole wheat dough (WWD) were investigated. The results showed that compared to the control, the content of ordered structure (β‐sheet) of gluten protein improved by 6.81% and the content of free sulfhydryl decreased by 63.73% respectively in WWD with 1% Aa p. Furthermore, the content of immobilized water increased up to 94.89% and the moisture distributed in the center of the dough had higher fluidity in WWD with 1% A ap. Moreover, the rheological properties of WWD including storage modulus and loss modulus were significantly increased with the addition of Aa p compared to the control. In addition, the tensile resistance and the stretching distance of the WWD with 1% Aa p improved by 68.01% and 12.65% respectively. Therefore, 1% Aa p significantly improved the quality of WWD by affecting moisture, starch, and protein fractions in the dough. Novelty impact statement: In this paper, it was found that Aa p could significantly improve the quality of WWD, solving the problems of poor viscoelasticity and low quality of WWD. The application of Aa p on WWD provided a theoretical basis and research ideas for the development of high‐quality whole wheat food.